Wishful thinking about consciousness - Grindrod, P (Springer, 2024)
We contrast three distinct mathematical approaches to the hard problem of consciousness: quantum consciousness, integrated information theory, and the very large scale dynamical systems simulation of a network of networks. We highlight their features and their associated hypotheses, and we discuss how they are aligned or in conflict. We suggest some challenges for the future theories, in considering how they might apply to the human brain as it develops both cognitive and conscious sophistication, from infancy to adulthood; and how an evolutionary perspective challenges the distinct approaches to aver performance advantages and physiological surrogates for consciousness.